Different MACS sorting strategies for the enrichment of Lin– (CD34+ CD45–) hematopoietic progenitor cells: preliminary study - Jaromír Vašíček (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2018)
Magnetic-activated cell sorting (MACS) has become a standard method for the isolation of hematopoietic stem/progenitor cells (HSC/HPC) in human or mouse model using CD34 antibodies. However, at the present there is no useable CD34 antibody that could be successfully used for the selection of rabbit HSC/HPC. Therefore, the aim of this preliminary study was to remove all mature cells (CD45+) from the heterogeneous mixture of rabbit peripheral blood and bone marrow mononuclear cells (PBMCs and BMMCs) in order to enrich these cell populations for the CD34+ cells. Briefly, cells were incubated with a CD45 antibody and proper magnetic microbeads. Three different MACS sorting strategies were used in the experiment that differed mainly in the sample loading rate and the number of used magnetic columns. Control (unsorted) and sorted cells were assessed for the sorting efficiency (% of double positive cells for CD45 and Labelling Check Reagent – LCR) by flow cytometry and for the relative expression of CD34 antigen by qPCR. According to flow cytometry, Depl025 mode showed the best sorting efficiency in terms of the lowest percentages of CD45+LCR+ cells for rabbit PBMCs as well as BMMCs. qPCR analysis confirmed this mode as the best in terms of the relative CD34 expression for rabbit PBMCs. However, higher relative expression of CD34 in BMMCs was obtained by other mode – Posselds. In conclusion, this study demonstrates a possible enrichment of rabbit (CD34+) HSC/HPC by the magnetic depletion of mature hematopoietic (CD45+) cells.